2013
DOI: 10.1094/pdis-10-12-0906-re
|View full text |Cite
|
Sign up to set email alerts
|

Spring Wheat Tolerance and Resistance to Heterodera avenae in the Pacific Northwest

Abstract: Smiley, R. . 2013. Spring wheat tolerance and resistance to Heterodera avenae in the Pacific Northwest Plant Dis 97-590-600.The cereal cyst nematode Heterodera avenae reduces wheat yields in the Pacific Northwest. Previous evaluations of cultivar resistance had been in controlled environments. Cultivar tolerance had not been evaluated. Seven spring wheat trials were conducted in naturally infested fields in three states over 2 years. A split-plot design was used for all trials. Five trials evaluated both toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…avenae was first detected in the United States in 1974, in western Oregon (20), and is now reported in seven western states that include the Pacific Northwest (PNW) states of Idaho, Oregon, and Washington (43). H. avenae has reduced yields of susceptible wheat cultivars by as much as 64% (43,46,48,50) and is estimated to reduce the profitability of wheat production by at least $3.4 million annually in the PNW (43).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…avenae was first detected in the United States in 1974, in western Oregon (20), and is now reported in seven western states that include the Pacific Northwest (PNW) states of Idaho, Oregon, and Washington (43). H. avenae has reduced yields of susceptible wheat cultivars by as much as 64% (43,46,48,50) and is estimated to reduce the profitability of wheat production by at least $3.4 million annually in the PNW (43).…”
mentioning
confidence: 99%
“…Wheat is therefore produced mostly in 2-year rotations that do not ade quately suppress the nematode density before the next crop of susceptible wheat is planted. Spring wheat cultivars with resistance to H. avenae were recently identified (47,48), but resistance to H. filipjevi has not been evaluated in the PNW. Research in other countries indicated that individual wheat cultivars may differ in their ability to serve as hosts of these two nematodes; cultivars resistant to H. avenae may not be resistant to H. filipjevi, and vice versa (29).…”
mentioning
confidence: 99%
See 3 more Smart Citations